Nghiên cứu thành phần hóa học loài hải miên Amorphinopsis excavans - Anh Tuấn, Hoàng Lê; Thúy Hằng, Đan Thị; Cúc, Nguyễn Thị; Hải Yến, Dương Thị; Dung, Dương Thị; Nhiệm, Nguyễn Xuân; Tài, Bùi Hữu; Quang, Trần Hồng; Nam, Nguyễn Hoài; Yến, Phạm Hải; Minh, Châu Văn; Kiệm, Phan Văn (Vietnam Journal of Chemistry, 2014)
From the methanol extract of Vietnamese marine sponge Amorphinopsis excavans, five known compounds, 24-methylcholestane-3β,5α,6β,25-tetrol 25-monoacetate (1), 24-methylcholestane-1b,3β, 5α, 6β,25-pentol 25-monoacetate (2), (2S)-1-O-(2′,3′,4′,5′-tetrahydroxycyclopentyl)-3-O-(10′′-methylhexadecyl)glycerol (3), thymine (4), and cholesterol (5) were isolated. Their structures were identified by various spectroscopic methods in comparison with the literature values. Compounds 1 and 2 were isolated from soft corals but from this genus for the first time. Keywords: Amorphinopsis excavans, Vietnamese marine sponge, polyhydroxysterol.